Cultural factors and risks: Incidence analysis of acute coronary syndrome in young adults in Bali - Bawa, Ngakan Nyoman Rai; Nurachmah, Elly; Adam, Muhamad; Herawati, Tuti; Sungkono (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Background: The prevalence of acute coronary syndrome (ACS), which is the most critical ischemic heart disease and is the main source of morbidity and mortality worldwide, increases significantly every year in Indonesia, including Balinese young adults. Identification of modifiable risk factors, such as smoking habits, consuming alcohol, and processed food, is culturally important for making primary prevention strategies, the occurrence of attacks, and secondary prevention to reduce readmissions.Objectives: This study aims to identify modifiable factors using a cultural approach associated with the incidence of ACS in Balinese young adults.Methods: This is a quantitative cross-sectional study. A total of 150 eligible respondents were recruited consecutively at the Integrated Heart Service Centre of Prof. Dr. I.G.N.G Ngoerah General Hospital, Bali. Data were collected using validated questionnaires on socio-demographics, diet (SQ-FFQ), physical activity (GPAQ), alcohol use (AUDIT), psychological status (DASS-42), and sleep quality (PSQI). Independent variables included hypertension, diabetes, dyslipidemia, hyperuricemia, lifestyle, and psychosocial factors, with ACS incidence as the outcome. Data were analysed with descriptive statistics, chi-square, and logistic regression (p < 0.05).Results: Results showed a significant relationship between hypertension, high salt intake, and sleep quality. Hypertension demonstrated the strongest statistical association with ACS among the variables included in the model (OR = 6.785, 95% CI: 2.429 - 18.956). The Nagelkerke R² value was 0.449, indicating a moderately strong predictive model. This shows that hypertension, risky diet, and poor sleep quality contribute to 44.9% of the explained variance in the incidence of ACS among young adults. Conclusion: Risk factors contribute to the high prevalence of hypertension in Bali, including a high salt and fat diet in Balinese cuisine, poor sleep habits, and traditional activities in Bali. Recommendations for future research include exploring cardio-social factors and culturally based prevention and control strategies for ACS in young adults in Bali.